(untitled) (UNIZIK Journal of Marketing, 2024)
This study investigated the relationship between business content creation and marketing performance in the context of television stations in South-south, Nigeria. The study employed a cross-sectional survey research design with an explanatory research design. A correlational method of investigation was employed. The study adopted the resource-based theory as the foundation of this study. The study population was the nineteen (19) television organizations doing business in the South-south region of Nigeria. A census study was made where the population was fully studied. However, three managers; marketing manager, programme manager and the general manager in each television organizations constituted the respondents of the study. Thus, fifty-seven (57) managers made up the study subjects. Data for the study were collected through primary source. Fifty-seven (57) copies of the questionnaire were distributed to the respondents, three (3) copies to the managers in each institution, marketing manager, programme manager and the general manager. After data validation, only fifty (50) copies were used for the study. The study made use of univariate and bivariate statistics for the data analysis with the aid of the statistical package for social science (SPSS), version 25.0. The findings of the study revealed that, business content creation positively and significantly correlates with value creation, customer retention and new market entry and significantly improve marketing performance of television stations in South-south, Nigeria. The study concludes that, business content creation significantly improves marketing performance of television stations in South-south, Nigeria. We therefore recommend that the management of the television companies in the South-south, Nigeria should develop and execute innovative business contents and making optimal investments in same. This will create value for customer retention, new market development and significantly improve marketing performance.